Clinical Features and Correlates of Poor Nighttime Sleepiness in Patients with Parkinson’s Disease - Xiaoling Qin; Xue Li; Gang Chen; Xu Chen; Mingyu Shi; Xue-kui Liu; Zai-li Li; Zai-e Xin; Dianshuai Gao (Parkinson's Disease)
Objective. The present study investigated the clinical features and correlates of poor nighttime sleepiness (PNS) in patients with Parkinson’s disease (PD). Methods. One hundred ten patients with PD (divided into PD-PNS group and PD-nPNS group) and forty-seven controls (nPD-PNS group) were enrolled in this study. Demographic information was collected. Patients were assessed according to the unified Parkinson’s disease rating scale (UPDRS) and Hoehn–Yahr (H&Y) stage scale. Patients were also evaluated according to the Pittsburgh sleep quality index (PSQI), Epworth sleepiness scale (ESS), rapid eye movement sleep behavior disorder screening questionnaire (RBD-SQ), restless leg syndrome (RLS) diagnosis, Hamilton’s depression scale (HAMD), and Hamilton’s anxiety scale (HAMA). Results. The prevalence of PNS was 55.45% (61/110) in patients with PD. The PD-PNS group tended to have a longer duration of disease, higher UPDRS-I and UPDRS-III scores, a higher percentage of RLS patients, and higher HAMA and HAMD scores than those of the PD-nPNS group. The PD-PNS group tended to have a higher percentage of RBD and RLS patients and higher HAMA and HAMD scores than those of the nPD-PNS group. Analysis of the PSQI components and PSQI impact factors showed that the PD-PNS group had worse subjective sleep quality (χ2 = −2.267, P = 0.023), shorter sleep latency (χ2 = −2.262, P = 0.024), fewer sleep medications (χ2 = −4.170, P ≤ 0.001), worse daytime functioning (χ2 = −2.347, P = 0.019), and an even higher prevalence of increased nocturia (χ2 = 4.447, P = 0.035), nightmares (χ2 = 7.887, P = 0.005), and pain (χ2 = 9.604, P = 0.002) than those of the nPD-PNS group. Analysis also indicated that the PSQI global score positively correlated with BMI (r = 0.216, P < 0.05), H&Y stage (r = 0.223, P < 0.05), UPDRS-I (r = 0.501, P < 0.01), UPDRS-III (r = 0.425, P < 0.01), ESS (r = −0.296, P < 0.01), RBD (r = 0.227, P < 0.05), RLS (r = 0.254, P < 0.01), HAMA (r = 0.329, P < 0.01), and HAMD (r = 0.466, P < 0.01). In the final model, H&Y stage, RLS, UPDRS-III, and HAMD remained associated with the PQSI score (P ≤ 0.001, P ≤ 0.001, P = 0.049, P ≤ 0.001, respectively). Conclusions. Our data showed that PNS was common in patients with PD. H&Y stage, UPDRS-III, HAMD, and RLS were positively associated with PNS. Attention to the management of motor symptoms, RLS, and depression may be beneficial to nighttime sleep quality in patients with PD.